The role of regional scenarios in CCAFS cross-scale research, planning and action toward improved food security, environments and livelihoods - Thornton, Philip K.; Vervoort, Joost M.; Förch, Wiebke; Ericksen, Polly J.; Kok, K.; Ingram J; Herrero, Mario; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Research and action toward better food security, environmental health and rural livelihoods under climate change in the developing world must deal with interacting natural and human systems change processes across multiple dimensions (e.g. biophysical, economic, policy, temporal) and scales (e.g. local, regional, short-term variability, long-term change) in food systems and their contexts. The CGIAR research program Climate Change, Agriculture and Food Security (CCAFS) engages in a wide range of research and capacity building activities focusing on climate change adaptation and mitigation across dimensions and scales. In this context, this document outlines the key potential of the CCAFS regional scenarios process as a tool for cross-scale and multi-disciplinary food systems research, planning and action.